Critical Thinking Skills and Preferred Learning Styles of Gifted Students at the Secondary Stage in Taif Governorate - Badrya Alotaibi; Abdulhamid Alarfaj (Umm Al-Qura University, 2022)
The study aimed to identify the level of critical thinking skills and the preferred learning styles of gifted students at the secondary stage in Taif Governorate, in addition to revealing the differences in critical thinking skills according to their different preferred learning styles and their gender. The sample of the study consisted of (192) male and female secondary school students in Taif Governorate schools, distributed by gender into (92) male and (100) female students. The Saudi short form of the Watson-Glaser Critical Thinking Test, and Kolb's Learning Styles Inventory were used after verifying their psychometric properties to collect data from the subjects. The results revealed a low level of gifted students' possession of critical thinking skills in general, and in particular the deduction skill. The results also revealed that there is a rate of (16.67%) gifted students who did not show preference of a specific learning style, and that the most preferred learning style was the divergent style, followed by the accommodator style, then the convergent style, and finally the assimilator style. The results also showed a statistically significant mean score differences attributed to gender on three subtests of the critical thinking test as well as the total score on the test as males outperformed females in the conclusion subtest while females outperformed males in the induction, evaluation of arguments, and the overall mean scores. The results also revealed a statis-tically significant mean score differences on all subtests as well as the overall mean score attributed to the preferred learning style in favor of the divergent style followed by the assimilator style, then the accommodator style, and finally the convergent style.